The Prevalence of Periodontal disease by Community Periodontal Index in type II-diabetic and non-diabetic patients - Amira Shahid, Nighat Zahid, Sadaf Qadeer, Saira Yousuf Dar, Maliha Muneer, Suffiyan Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with type II- Diabetes Mellitus show macrovascular&microvascular complications including Periodontitis. Aim: To assess periodontal disease prevalence by Community Periodontal Index(CPI)in type II-diabetic and non-diabetic patients. Study design: Cross-sectional comparative study. Place and duration: Dental Out-patient Department at Madina Teaching Hospital, Faisalabad in three months duration. Methodology: CPIprobe (WHO probe) was used to record Community periodontal Index in seventy type-II diabetic and seventy non-diabetic subjectsfor assessment the periodontal disease.The data was collected and SPSS Version 22was used foranalyzing the data. Results: Mean age was 56 years (range 31- 73) diabetic and 46 years (range 20-67) in non-diabetic group. There were more male subjects in both groups. In the non-diabetic group, subjects with good oral hygiene were 13(18.6%). In the diabetic subjects 30(7.14%) had code 3 and 9(2.14%) had code 4. There were 20(4.76%) diabetic subjects and17(4.05%) nondiabetic subjects with missing teeth. Conclusion: Within the study population and limits, diabetic subjects are more likely to have severe periodontal destruction so regular periodontal assessment and treatment must be a part of their management protocol. Keywords: Periodontal disease, Community Periodontal Index, Diabetic mellitus type-II